Motor, cognitive, and functional declines contribute to a single progressive factor in early HD. (12th December 2017) - Schobel, Scott A.; Palermo, Giuseppe; Auinger, Peggy; Long, Jeffrey D.; Ma, Shiyang; Khwaja, Omar S.; Trundell, Dylan; Cudkowicz, Merit; Hersch, Steven; Sampaio, Cristina; Dorsey, E. Ray; Leavitt, Blair R.; et al.
Abstract : Objective: To identify an improved measure of clinical progression in early Huntington disease (HD) using data from prospective observational cohort studies and placebo group data from randomized double-blind clinical trials. Methods: We studied Unified Huntington Disease Rating Scale (UHDRS) and non-UHDRS clinical measures and brain measures of progressive atrophy in 1, 668 individuals with early HD followed up prospectively for up to 30 to 36 months of longitudinal clinical follow-up. Results: The results demonstrated that a composite measure of motor, cognitive, and global functional decline best characterized clinical progression and was most strongly associated with brain measures of progressive corticostriatal atrophy. Conclusions: Use of a composite motor, cognitive, and global functional clinical outcome measure in HD provides an improved measure of clinical progression more related to measures of progressive brain atrophy and provides an opportunity for enhanced clinical trial efficiency relative to currently used individual motor, cognitive, and functional outcome measures.